Environmental and energy performances of the Italian municipal solid waste incineration system in a life cycle perspective. Issue 2 (February 2022) - Sisani, Federico; Maalouf, Amani; Di Maria, Francesco
The environmental and energy performances of the Italian municipal solid waste incineration (MSWI) system was investigated by a life cycle assessment approach. On average the 39 MSWIs operating in Italy in 2018 treated about 6, 000, 000 Mg of residual municipal solid waste (RMSW) recovering on average from 448 kWh Mg −1 RMSW to 762 kWh Mg −1 RMSW of electricity and from 732 kWh Mg −1 RMSW to 1102 kWh Mg −1 RMSW of heat. The average quantity of CO2 eq Mg −1 RMSW emitted ranged from about 800 up to about 1000 depending on the size and on the energy recovery scheme of the facility. Avoided impacts (i.e., negative values) were detected for the kg PM2, 5eq Mg −1 RMSW and for human health (disability-adjusted life year Mg −1 RMSW). The determination of the hybrid primary energy index (MJ Mg −1 RMSW) indicated that mainly large size facilities and those operating according to a power and heat energy recovery scheme are effectively able to replace other primary energies by the exploitation of the lower heating values of the RMSW.